2008
DOI: 10.1002/atr.5670420103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of driver satisfaction of travel information on variable message signs using fuzzy aggregation

Abstract: Driver satisfaction regarding travel information provided by variable message signs (VMS), which are part of the NamMountain Tunnel ATIS, was evaluated using fuzzy aggregation. Application of fuzzy aggregation to analyze driver satisfaction allows one to represent the variability and complexity of human perception with great fidelity. A fuzzy weighted average using two sets of fuzzy membership functions was applied to evaluate individual satisfactions of delay and travel time information provided. Then, those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Drivers' satisfaction is influenced by many factors, stretching from personal issues to road environment, quality of the service, working environment, psychological aspects, and community issues. Based on an investigation of the effects of road traffic operation, Lee et al [42] found that the overall satisfaction that drivers generally perceive relates to drivers' route-changing behaviours. The quality of the service, which can be expressed by internal service quality, has a positive effect on employees' satisfaction, commitment, and wellbeing, which in turn positively influence employees' performance [43].…”
Section: Job Satisfaction and Outcome Of Ride-sourcing Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Drivers' satisfaction is influenced by many factors, stretching from personal issues to road environment, quality of the service, working environment, psychological aspects, and community issues. Based on an investigation of the effects of road traffic operation, Lee et al [42] found that the overall satisfaction that drivers generally perceive relates to drivers' route-changing behaviours. The quality of the service, which can be expressed by internal service quality, has a positive effect on employees' satisfaction, commitment, and wellbeing, which in turn positively influence employees' performance [43].…”
Section: Job Satisfaction and Outcome Of Ride-sourcing Driversmentioning
confidence: 99%
“…The proposed model and hypotheses were developed based on the literature in the previous section. Job satisfaction is influenced by home-related concerns [10] and work-related concerns [10,21,42,43], and psychological resources that meet the criteria for positive organizational behaviour [50] include hope, efficacy, optimism, and resilience [51]. Avey et al [46] show the positive relationships between psychological capital and desirable employee attitudes (job satisfaction, organizational commitment, psychological wellbeing); desirable employee behaviours (citizenship); and multiple measures of performance (self, supervisor and objective evaluations), including undesirable employee attitudes (cynicism, turnover intention, job stress, and anxiety) and undesirable employee behaviours (deviance).…”
Section: Proposed Model Constructmentioning
confidence: 99%
“…Lee, Lee, and Pietrucha (2008) explored the driver satisfaction to delay information and travel-time information provided by the VMS. Bonsall (1992), Polydoropoulou, Ben-Akiva, and Kaysi (1994), Zhao, Muromachi, Harata, and Ohta (1995), Hato, Taniguchi, and Sugie (1997), Abdel-Aty, Kitamura, and Jovanis (1997), Chen, Srinivasan, and Mahmassani (1999), Peeta, Ramos, and Pasupathy (2000), Srinivasan and Mahmassani (2000), Chen and Jovanis (2003), Zhenlong andChonglun (2011), andZhong, Zhou, Ma, andJia (2012) discussed the impact of information quality, reliability, and accuracy on the travel behaviour of drivers.…”
Section: Review Of Relevant Workmentioning
confidence: 99%
“…Lee et al, (2010) applied the fuzzy set theory along with the AHP and TOPSIS method to evaluate the service quality of online auction. Lee, D et al (2008) studied the performance of IT department in the manufacturing industry in Taiwan. Buyukozkan et al (2008) proposed fuzzy AHP method to evaluate e-logistics based strategic alliance partners.…”
Section: Applications Of Fuzzy Ahpmentioning
confidence: 99%